Impact of microcrystalline cellulose extracted from walnut and apricots shells on the biodegradability of Poly (lactic acid) - Mahmoud, Yasmine; Belhanche-Bensemra, Naima; Safidine, Zitouni (Frontiers in Materials, 2022)
In this work, various microcrystalline celluloses were extracted from apricots shells (AC) and walnut shells (WC) by alkaline treatments combined with hydrogen peroxide blanching. Different composites-based poly (lactic acid) (PLA) and microcrystalline cellulose PLA/AC and PLA/WC were successfully prepared by the cast-solution method with various PLA/AC and PLA/WC ratios. PLA and prepared composites were characterized by tensile test, Fourier transform infrared spectroscopy (FTIR), melt flow index (MFI), thermo gravimetric analysis (TGA), differential scanning calorimetry (DSC) and scanning electron microscopy (SEM). Results showed an increase in Young’s modulus from 802.6 MPa (PLA) to 1412.9 MPa (10% AC) and to 1145,6 MPa (7% WC) in PLA composites. A decrease in degradation temperature was recorded with increasing microcrystalline cellulose percentage in PLA composites from 354°C (PLA) to 328°C (PLA/10% AC) and 339°C (PLA/10% WC). An enhancement in crystallinity rate was observed after incorporation of the microcrystalline cellulose from 30.42% (PLA) to 37.97% (PLA/7% WC) and 38.47% (PLA/10% AC). Furthermore, the biodegradation was evaluated by a soil burial test. A loss in composites weights of 38% (PLA/7% WC), 13% (PLA/7% AC) and 14% (PLA) was obtained after 12 months within soil burial test. Finally, the presence of MCC extracted from walnut shells in PLA matrix at 7% of content exhibited the best mechanical properties, crystalline structure and biodegradability rate.